The development of mobile augmented reality : 3-dimensional video / Nur Nabihah Mohamad Nizar ... [et.al.] - Mohamad Nizar, Nur Nabihah; Rahmat, Mohd Khairezan; Maaruf, Siti Zuraida; Damio, Siti Maftuhah (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Augmented reality has become one of the learning processes applicable through mobile devices, called Mobile Augmented Reality (MAR). Learning and service experiences can be enhanced using mobile devices such as those offered by MAR, an innovative learning space providing active interaction of superimposing digital content into the real world. Previous studies have discussed the importance of the MAR system in various domains, especially in education, as it led students to achieve higher levels of engagement in their learning process. However, there are limitations in highlighting the importance of the development process for MAR. Therefore, this present study describes the development process of MAR through the AREM model, which aimed to exhibit the systematic guidelines in producing a practicable MAR. It also highlights the preferable learning content and media component based on the respondents' responses in the survey questionnaire. Data gathered from questionnaires were analysed by using descriptive statistics. The guideline in developing MAR can benefit students and educators in producing a MAR for learning purposes.